The Oral Health and Comorbid Diseases Knowledge Between Urban and Rural Community during Pandemic - Wahyuni, Indah Suasani; Herawati, Irma Erika; Puspitasari, Irma Melyani; Mutakin, Mutakin; Milanda, Tiana; Levita, Jutti (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2022)
The restriction of social mobility and activity during the COVID-19 pandemic has been implemented to stop the deadly transmission of the SARS-CoV2 virus. People are forced to stay at home and strictly perform the COVID-19 health protocol in their daily activities. Currently, a continuous self-maintenance of the health, including oral health, is considered the best strategy worldwide. This community service activity aimed to assess the knowledge of the urban and rural adult community about oral health, comorbidity, and the quality of life (QoL) during this pandemic situation by using a pre-and post-test quasi-experimental design with an intervention of health-knowledge sharing using leaflets and videos, and a WHOQOL 2012 questionnaire to study the QoL. Paired t-test was used as statistical analysis. Total respondents were 131 (n = 76 for urban and n = 55 for rural), selected using the purposive sampling method. There was a significant difference between the results of the pre-test and post-test in both urban and rural groups (t count ranged from 1.69 to 5.98; p 0.05). Based on the WHOQOL 2012 questionnaire, both urban (90.79%) and rural (87.27%) respondents indicated a good QoL, while the remaining was scored as medium. Physical conditions/pain was the main domain that directly affects the QoL in both communities. It could be concluded that the knowledge-sharing intervention to the community gave a good impact in enhancing the knowledge of the respondents, however, a continuous program should be further carried out for better results.